2004
DOI: 10.1002/j.2161-1920.2004.tb00884.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of life role salience on life satisfaction

Abstract: The authors examined the relationships among life role salience, role strain, coping efficacy, and life satisfaction for adults (N = 125) who combine multiple life roles. Causal modeling procedures were used to test hypotheses based on D. E. Super's (1980, 1990) life‐span, life‐space theory and the social cognitive career theory (R. W. Lent, S. D. Brown, & G. Hackett, 2000). They hypothesized that high role salience would be related to high levels of role strain and that coping efficacy would mediate the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 36 publications
(37 reference statements)
2
24
0
2
Order By: Relevance
“…In other words, considerable time invested in and more emotion attached to marital role lead to energy consumption, which in turn increases exhaustion based on high job demands as a condition that also needs energy. This is consistent with the reported positive link between psychological commitment to the role and role strain [9] and with the assumption of role theory that multiple life roles result in the inter-role conflict when individuals experience difficulty performing each role successfully because of conflicting demands [1].…”
Section: Ijomeh 2018;31(3) 287supporting
confidence: 90%
See 2 more Smart Citations
“…In other words, considerable time invested in and more emotion attached to marital role lead to energy consumption, which in turn increases exhaustion based on high job demands as a condition that also needs energy. This is consistent with the reported positive link between psychological commitment to the role and role strain [9] and with the assumption of role theory that multiple life roles result in the inter-role conflict when individuals experience difficulty performing each role successfully because of conflicting demands [1].…”
Section: Ijomeh 2018;31(3) 287supporting
confidence: 90%
“…It has been reported that this is especially true when engagement requires substantial time. Similarly, Perrone and Civiletto [9] found that only role commitment as one of the 3 aspects of role salience was a significant contributor to role strain, explaining that probably participation in a role or value expectations about a role did not necessarily lead to role strain, but it was psychological commitment to the role that related to role strain. In addition, they reported that role strain affected life satisfaction indirectly through coping efficacy [9].…”
Section: Life Satisfaction and Exhaustionmentioning
confidence: 92%
See 1 more Smart Citation
“…Cette distinction n'est, toutefois, pas toujours précisée dans les écrits portant sur les conflits entre le travail et la famille. Lorsque ces concepts sont considérés de façon différenciée, l'engagement dans les rôles semble plus associé aux conflits entre le travail et la famille que la valorisation de ces derniers (O'Neil et Greenberger, 1994;Perrone et Civiletto, 2004). Cette distinction a mené certains auteurs à privilégier, aux fins d'étude, la notion d'engagement dans les rôles plutôt que celle de la valorisation (Campbell et Campbell, 1995;Fournier, Lachance et Bujold, 2009 (Fournier et al, 2009), se sont intéressés aux profils d'engagement dans le rôle de travailleur et divers rôles familiaux, ces derniers étant identiques à ceux de Lachance et ses collaborateurs (2006).…”
Section: Engagement Dans Les Rôlesunclassified
“…The central roles constitute the "core of who the individual is; are fundamental for the identity and essential for life satisfaction" (Savickas, 2002, p. 159). The multiplicity of roles can bring about confl ict and distress, as well as fulfi llment and life satisfaction (Super, 1980), since it can trigger diffi culties of commitment to any of them (Biggs & Brough, 2005;Frone, Russel, & Barnes, 1996;Ng & Feldman, 2007;O'Neil & Greenberger, 1994;Perrone & Civiletto, 2004;Super, 1980;Thoits, 1983) or allow the individual to realize to their interests, needs and values through the various roles, as the positive experience in a central role can affect the performance of others (Barnett, 1994;Cool, 1990;Cool et al, 1996). This relationship between the simultaneous performance of roles has been associated with the possibility of managing their demands (Grönlund, 2007;Perrone, AEgisdóttir, Webb, & Blalock, 2006;Possatti & Dias, 2002).…”
mentioning
confidence: 99%